Networks that Govern Cardiomyocyte Proliferation to Facilitate Repair of the Injured Mammalian Heart - Daniel J. Garry; Jianyi (Jay) Zhang; Thijs Larson; Hesham A. Sadek; Mary G. Garry (Methodist DeBakey Cardiovascular Journal)
Cardiovascular diseases are the number one cause of death worldwide and in the United States (US). Cardiovascular diseases frequently progress to end-stage heart failure, and curative therapies are extremely limited. Intense interest has focused on deciphering the cascades and networks that govern cardiomyocyte proliferation and regeneration of the injured heart. For example, studies have shown that lower organisms such as the adult newt and adult zebrafish have the capacity to completely regenerate their injured heart with restoration of function. Similarly, the neonatal mouse and pig are also able to completely regenerate injured myocardium due to cardiomyocyte proliferation from preexisting cardiomyocytes. Using these animal models and transcriptome analyses, efforts have focused on the definition of factors and signaling pathways that can reactivate and induce cardiomyocyte proliferation in the adult mammalian injured heart. These studies and discoveries have the potential to define novel therapies to promote cardiomyocyte proliferation and repair of the injured, mammalian heart.